Enhanced in vivo antimalarial activity of artemether by clotrimazole against drug-sensitive and resistant Plasmodium berghei - Kenechukwu , Franklin C.; Momoh , Mumuni A.; Ugwuoke , Wilfred I.; Nnamani , Daniel O.; Nwobodo , Joy I.; Ogbonna , Jude E.; Nzekwe , Ezichim F.; Nweke , Linda C.; Obila , Mary U.; Odoh , Tochukwu; Odo, Bonaventure A.; Nwagwu , Chinekwu S.; et al. (Journal of Drug Delivery and Therapeutics, 2025)
The emergence of resistance parasites to currently approved artemisinin-based combination therapies (ACTs) highlight the need for regimens incorporating repurposed antimalarials. In this study, we investigated the in vivo performance of artemether/clotrimazole combination against chloroquine-sensitive and multidrug-resistant Plasmodium berghei (Pb) in a preclinical mouse model. The antimalarial activity of artemether, clotrimazole and combination of artemether (8 mg/kg) and clotrimazole (2 mg/kg) was investigated using standard protocols for uncomplicated malaria (UM) and severe malaria (SM) in mice infected with chloroquine-sensitive Pb (CPb) and Pb ANKA (PbA), respectively. Hematological parameters (white blood cells, red blood cells, packed cell volume and haemoglobin) and lethality of infected mice in comparison with controls, tested in parallel, were also monitored. The reduction in parasitemia caused by peroral (p.o.) administration of artemether/clotrimazole combotherapy in CPb-infected mice was significantly greater than artemether monotherapy (**p